Photodynamic therapy for oral mucositis in cancer patients- a systematic review and meta-analysis - Betsy Joseph; Matti Mauramo; Baiju Kamalasanan Vijayakumary; Tuomas Waltimo; Sukumaran Anil; Timo Sorsa (Photodiagnosis and Photodynamic Therapy)
Aim: This systematic review aimed to evaluate the efficacy of photodynamic therapy (PDT) in reducing the severity of chemotherapy-induced oral mucositis, and associated symptoms in cancer patients compared to standard care or other interventions. Materials and methods: A comprehensive literature search identified seven relevant studies (randomized controlled trials and non-randomized clinical trials) published between January 1, 2000, and May 31, 2024. The data analysis was carried out using the standardized mean difference as the outcome measure. A random-effects model was fitted to the data. The rank correlation test and the regression test, using the standard error of the observed outcomes as predictors, were used to check for funnel plot asymmetry. Results: Studies combining PDT with photobiomodulation therapy (PBMT) consistently showed superior therapeutic outcomes compared to PBMT alone, particularly in accelerating healing and reducing pain. In the meta-analysis (k = 4), the observed standardized mean differences ranged from -0.9605 to -0.0223, with most estimates being negative (100 %). The estimated average standardized mean difference based on the random-effects model was -0.5138 (95% CI: -0.8799 to -0.1477). Conclusion: PDT, especially when combined with PBMT, shows promise in reducing the severity of oral mucositis and associated symptoms in cancer patients.